2018
DOI: 10.1016/j.metabol.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime light exposure enhances Rev-erbα-targeting microRNAs and contributes to hepatic steatosis

Abstract: Thus, altered miRNAs profile is an important mechanism underlying the disruption of the peripheral clock caused by exposure to ALAN, which could lead to hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Constant light did not influence total 24 h food intake [51,61,62,[73][74][75], but the daily variation was suppressed mostly due to increased food consumption in mice during the subjective day [51,61,62,73,74]. On the other hand, total food intake was reduced in mice fed a high-fat diet [61].…”
Section: Food Intake and Body Mass Under Constant Lightmentioning
confidence: 86%
See 4 more Smart Citations
“…Constant light did not influence total 24 h food intake [51,61,62,[73][74][75], but the daily variation was suppressed mostly due to increased food consumption in mice during the subjective day [51,61,62,73,74]. On the other hand, total food intake was reduced in mice fed a high-fat diet [61].…”
Section: Food Intake and Body Mass Under Constant Lightmentioning
confidence: 86%
“…In mice, most studies have shown the loss of daily variation in metabolic measures due to LL conditions (Table 1). Insulin sensitivity was diminished during the subjective night, causing the loss of diurnal variation [51,61], which is in line with changes in insulin and glucose levels [51], as well as endogenous glucose production [61]. Glucose tolerance was impaired during the subjective day [62,74].…”
Section: Glucose and Lipid Metabolism Under Constant Lightmentioning
confidence: 90%
See 3 more Smart Citations